Biological peculiarities and cultivation of groundnut (a review) - N. V. Kishlyan; V. D. Bemova; T. V. Matveeva; V. A. Gavrilova (Труды по прикладной ботанике, генетике и селекции)
Peanut is one of the most important crops in the Fabaceae Lindl. (Leguminosae L.) family. South America is considered to be the homeland of peanut, but now this crop is cultivated in America, Africa, Australia, Europe and Asia. The modern phylogenetic system of the genus Arachis L. includes 79 wild species and one cultivated species of common peanut (A. hypogaea L.). Diploid species contain 2n = 20 chromosomes of the A, B or D genome, tetraploids have A and B genomes. The А and В genomes are sequenced. Special biological features of all peanut varieties are the presence of chasmogamous and cleistogamous flowers and the development of pods only underground (geocarpy). Along with high requirements for improving the quality of oil and food products, much attention is paid to their safety: resistance to aflatoxin contamination and mitigation of allergenicity. Peanut cultivars vary in plant habit, shape and color of pods and seeds. Their growing season in Africa, Latin America and Asia is from 160 to 200 days, so early-ripening forms need to be selected for the south of the Russian Federation. Breeders from the Pustovoit Institute of Oil Crops (VNIIMK) have developed peanut cultivars with a yield of 2.0–3.3 t/ha and growing season duration of 115–120 days, adaptable to the environments of Krasnodar Territory. At present, there is no large-scale peanut production in Russia, nor any breeding efforts are underway. As for the world, along with conventional breeding practices (individual selection, intra- and interspecies crosses, etc.), peanut is widely involved in genomic studies. A number of cultivars highly resistant to pests, diseases and drought have been released. Over 15,000 peanut accessions are preserved in the world’s gene banks, including 1823 accessions in the collection of the Vavilov Institute (VIR). Utilization of the worldwide genetic resources of peanut and use of modern research technologies will contribute to the revival of peanut cultivation in Russia.